Hindu and Classical Ancient virtues in a comparative perspective - Shokhin, Vladimir (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. I, Bogoslovie, filosofii͡a, 2023)
The author claims that Graeco-Roman, Hindu and Chinese catalogues of virtues have much more common with each other than what is permitted by contemporary agnosticism in cultural studies which has only the appearance of wisdom. As to the differences, they are connected with the soteriological intention behind the Hindu catalogues while the Greek (before Neoplatonism) and Chinese ones label the development of secular personal dignity and social responsibility. The author does not conceal his preferences as well while asserting that the quadrangle of cardinal virtues as developed in Platonism had evident advantages in consistency over its Aristotelean restructuring via the division of virtues into intellectual and moral ones. He also is sure that this quadrangle was immensely improved in its Latin version by Cicero and Apuleius by means of narrowing the “multi-seated” Greek concept of sophrosyne up to “single-seated” temperantia. The initial Christian receptions of Graeco-Roman cardinal virtues are also estimated, and an alternative of their inbuilding into one of three human vocations in accordance with three Jesus Christ’s ministries is offertd. The author claims that Graeco-Roman, Hindu and Chinese catalogues of virtues have much more common with each other than what is permitted by contemporary agnosticism in cultural studies which has only the appearance of wisdom. As to the differences, they are connected with the soteriological intention behind the Hindu catalogues while the Greek (before Neoplatonism) and Chinese ones label the development of secular personal dignity and social responsibility. The author does not conceal his preferences as well while asserting that the quadrangle of cardinal virtues as developed in Platonism had evident advantages in consistency over its Aristotelean restructuring via the division of virtues into intellectual and moral ones. He also is sure that this quadrangle was immensely improved in its Latin version by Cicero and Apuleius by means of narrowing the “multi-seated” Greek concept of sophrosyne up to “single-seated” temperantia. The initial Christian receptions of Graeco-Roman cardinal virtues are also estimated, and an alternative of their inbuilding into one of three human vocations in accordance with three Jesus Christ’s ministries is offertd.